2018
DOI: 10.3747/co.25.3827
|View full text |Cite
|
Sign up to set email alerts
|

Implementation Considerations Using HPV Self-Collection to Reach Women Under-Screened for Cervical Cancer in High-Income Settings

Abstract: The success of cytology (Pap screening) programs is undeniable and has drastically reduced cervical cancer rates in high-income settings where it has been implemented 1 . However, cytology for primary cervical cancer screening has a number of limitations including poor sensitivity, a taxing demand on human and operational infrastructure, high health system costs, and limited uptake rates, leading researchers and policy-makers to question whether further gains in public health are possible using this approach 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 41 publications
1
19
1
Order By: Relevance
“…This was due to their concerns of not administering the procedure correctly, having to conduct the self-collection at a health care clinic and having to re-screen if HPV was detected. These findings differ from several other studies conducted in developed and developing countries in which self-collection was found to be effective in increasing participation in the cervical screening programs among under screened or never screened women either in the clinical setting or at home [36] , [37] , [38] , [39] , [40] , [41] , [42] . To explore the differences between our findings and other studies further research is required.…”
Section: Discussioncontrasting
confidence: 99%
“…This was due to their concerns of not administering the procedure correctly, having to conduct the self-collection at a health care clinic and having to re-screen if HPV was detected. These findings differ from several other studies conducted in developed and developing countries in which self-collection was found to be effective in increasing participation in the cervical screening programs among under screened or never screened women either in the clinical setting or at home [36] , [37] , [38] , [39] , [40] , [41] , [42] . To explore the differences between our findings and other studies further research is required.…”
Section: Discussioncontrasting
confidence: 99%
“…Collection of a clinician-collected cervical screening test requires women or other people with a cervix (hereafter referred to as screening participants) to undergo a speculum examination performed by a practitioner to visualize the cervix and take a cervical sample. For people who are not screening at recommended intervals, there is a significant body of work describing the personal, practical and system-level barriers to clinician-collected cervical screening test, including embarrassment about undergoing a pelvic examination, 16 cultural barriers, 17 a history of trauma or sexual abuse 18 or a lack of time to attend primary care for screening. 19 Some of these barriers, particularly personal barriers which relate to the nature of the clinician-collected cervical screening test, can be addressed through self-collected cervical screening, where a screening participant can use a flocked swab to take their own HPV sample from their vagina.…”
Section: Introductionmentioning
confidence: 99%
“…[10]. Using self-collection, a woman can take the sampling device, insert it into her own vagina to collect a specimen, and then return it to a healthcare provider (either directly or through the mail) without the physical intervention of a healthcare practitioner [11]. This sample can then be processed using a nucleic acid test for the presence of HPV DNA or RNA.…”
Section: Introductionmentioning
confidence: 99%